حوكمة الجهاز المصرفي ودوره في تعزيز القدرة تنافسية للبنوك الجزائرية - حبيب, على (My University, 2016)
ملخص الدراسة: بسبب الانهيارات المالية التي حصلت في اقتصاديات بعض الدول الكبرى و الفضائح المالية لكبرى الشركات العالمية كشركة ENRON و كذلك التحول إلى نظام السوق المفتوح , زاد الاهتمام بقضية الحوكمة خاصة من قبل السلطات الإشرافية و الرقابية و المنظمات الدولية و قطاع المصارف , فأصدرت كل من منظمة التعاون الاقتصادي و التنمية و لجنة بازل للرقابة المصرفية أوراقا دولية تتضمن معايير تبني الحوكمة في المؤسسات المالية و المصرفية لتصبح بعدها بمثابة قواعد دولية تعمل ا معظم الدول للحفاظ على سلامة الأنظمة المصرفية . و سنتناول في هذه الدراسة أهم النقاط المتعلقة بالحوكمة بصفة عامة و الحوكمة في البنوك بصفة خاصة , و أعمال لجنة بازل للرقابة المصرفية في مجال الحوكمة في القطاع المصرفي , ثم سنتطرق إلى واقع الحوكمة وفق مبادئ لجنة بازل في القطاع المصرفي الجزائري و الآثار الإيجابية المترتبة عن تبني هذه المبادئ , حيث أبدت السلطات الإشرافية في الجزائر اهتماما بتبني مفهوم الحوكمة و تطبيق قواعدها , فقامت بإصلاحات و وضعت مجموعة من الأنظمة و القوانين المتعلقة بإدارة المخاطر و الرقابة الفعالة و التي تساعد على توفير البيئة المناسبة لتبني قواعد الحوكمة لتعزيز القدرة التنافسية. الكلمات المفتاحية : الحوكمة , الجهاز المصرفي الجزائري,قدرة تنافسية Abstract: Because of the financial collapses that occurred in the economies of some major countries and financial scandals of major international companies as ENRON; also the shift to the open market system, increased attention to the issue of governance especially by the supervisory authorities and regulators; international organizations and the banking sector. Each of anization of Economic Cooperation and Development (OECD) and the Basel Committee on Banking Supervision issued international work papers about the adoption of corporate governance's standards in banks and financial institutions to become then international rules that most of the countries adopt to maintain the integrity of banking systems.And we wille discuss in this study the most important points related to governance in general; and corporate governance in banks in particular, and the work of the Basel gommittee on Banking Supervision in the field of corporate governance in the banking sector, then we will look at the reality of corporate governance in the accordance with the principles of the Basel gommittee on Algerian banking sector and the positive effects of adopting these principles, where the supervisory authorities showed interest in Algeria to adopt the concept of corporate governance and the application of its rules so she reforms and developed a set of regulations and laws relating to risk management and effective control which helps to provide a suitable environment for the adoptions of the rules of corporate governance building a competitive advantage. Keywords: Corporate governance, banking sector in Algeria,competitive advantage.
دراسة حالة BNA
Keywords: BNA-حوكمة -الجهاز المصرفي -ودور-- تعزيز -القدرة تنافسية -للبنوك الجزائرية